Posterolateral Rotatory Knee Instability—MRI Evaluation of Anatomic Landmarks for Tibial Drill Tunnel Placement in Open and Arthroscopic Popliteus Tendon Reconstruction - Krause, Matthias; Akoto, Ralph; Drenck, Tobias Claus; Frosch, Karl-Heinz; Preiss, Achim (The Journal of Knee Surgery, 2019)
Anatomic reconstruction of the popliteus tendon and arcuate complex results in superior functional and a biomechanically more stable outcome compared with extra-anatomic techniques in posterolateral rotatory knee instability. Although specific characteristics of the femoral and fibular footprint of the anatomic posterolateral reconstruction have been described, data for tibial tunnel placement while popliteus tendon reconstruction do not exist. The purpose of this study was to quantify reasonable parameters, which could be used in arthroscopy, fluoroscopy, or open surgery to determine the anatomic tibial drill tunnel position in popliteus tendon reconstruction. Thirty magnetic resonance images of 30 patients with an intact posterolateral corner (PLC) were analyzed to specify the ideal point for tibial fixation of a popliteus tendon graft with respect to 17 bony, cartilaginous, and ligamentous anatomic landmarks. The ideal point for tibial fixation was defined as the musculotendinous junction of the popliteus tendon near to the insertion of the popliteofibular ligament. In the coronal plane, the ideal tibial fixation was located at the crossing of a tangent to the fibular head, parallel to the joint line with a tangent to the medial border of the fibular head, and vertical to the joint line with a deviation of less than 1 mm. It was located 0.26 (±1.91) mm superior to the distal edge and 11.75 (±2.66) mm lateral to the lateral edge of the tibial posterior cruciate ligament footprint and only 8.68 (±2.81) mm lateral to the lateral edge of the neurovascular bundle. Interrater reliability to detect the correct position of the popliteus tendon graft footprint was almost perfect. The position for tibial drill tunnel placement in anatomic popliteus tendon reconstruction showed low interindividual differences. The present findings of the quantified anatomic landmarks might improve open, fluoroscopy, or arthroscopy guided PLC reconstruction.
Keywords: posterolateral corner; popliteus tendon; MRI; anatomic technique; posterior; knee instability